Mulberry leaf polysaccharide improves cyclophosphamide-induced growth inhibition and intestinal damage in chicks by modulating intestinal flora, enhancing immune regulation and antioxidant capacity - Cheng, Ming; Shi, Yongbin; Cheng, Yumeng; Hu, Hongjie; Liu, Song; Xu, Yanping; He, Lingzhi; Hu, Shanshan; Lu, Yujie; Chen, Fengmin; Li, Jiang; Si, Hongbin (Frontiers in Microbiology, 2024)
Mulberry leaf polysaccharides (MLP) are the main active substances in mulberry leaves, but there is limited research on whether MLP can improve chicken immune suppression caused by cyclophosphamide (CTX). We investigated whether MLP can improve CTX induced immunosuppression and intestinal injury in chicks. According to our research, MLP significantly enhances the growth performance of chicks and significantly enhances the secretion of cytokines(IL-1β, IL-10, IL-6, TNF-α, IFN-γ), immunoglobulins, and antioxidant enzymes in the serum of immunosuppressed chicks. MLP can alleviate jejunal injury in chicks and increase the level of tight junction protein in the jejunum. Meanwhile, MLP activated TLR4-MyD88-NF-κB pathway in the jejunum . In addition, MLP treatment increased the species abundance of gut microbiota and alleviated CTX induced dysbiosis of gut microbiota. In summary, this study provides a scientific basis for MLP as an immune enhancer to enhance the growth performance of chicks and protect intestinal health.